Essential Oil of Ocimum gratissimum L. (Lamiaceae) as Biopreservative of Peanuts in Post-harvest: Application Model and Effects on Quality of Derived Products - Adjou, Euloge Sènan; Zossoungbo, Marielle; Totcheme, Omar; SOUMANOU, MANSOUROU MOHAMED (My University, 2022)
The aim of this study was to investigate the use of essential oil extracted from leaves of African basil (Ocimum gratissimum L.) in post-harvest preservation of peanuts as well as the effects on the physicochemical, technological and organoleptic characteristics of derived peanut products. Preservation tests of peanuts with essential oil of Ocimum gratissimum at a concentration of 0.6 μl/g were carried out. Control was without essential oil. Evolution of the fungal flora as well as physicochemical, technological and organoleptic characteristics of preserved peanuts were evaluated. Results of microbiological analyses indicated a significant reduction (p <0.005) of the microbial quantum in peanut samples preserved with essential oil, when compared to the control. The results of physicochemical analyses revealed that preservation of peanuts using essential oil of Ocimum gratissimum had little effect on the physicochemical characteristics. However, results from evaluation of the technological aptitudes of preserved peanuts indicated that the essential oil has modified the functional properties of preserved peanut samples, with a particular impact on the elasticity of the pastes as well as the flavor and the texture of the peanut cakes. Organoleptic analyses revealed that preservation of peanuts with the essential oil of Ocimum gratissimum affected the aroma and flavor of derived products.
Keywords: Arachis hypogaea L.; Ocimum gratissimum L.; essential oil; fungal flora; qualities; Benin